Downregulation of long noncoding RNA SNHG6 rescued propofol-induced cytotoxicity in human induced pluripotent stem cell-derived cardiomyocytes - Ren, Zhongguo (Cardiovasc Diagn Ther, 2020)
BACKGROUND: Propofol (PPF) overdose is a rare but lethal condition, which may lead to severe cardiac failure. In this study, we established an in vitro PPF-induced cardiac cytotoxicity model, and investigate the functional role of long non-coding RNA (lncRNA) small nucleolar RNA host gene 6 (SNHG6). METHODS: Human induced pluripotent stem cell-derived cardiomyocytes (HiPSC-CMs) were exposed to PPF in vitro. PPF-induced cytotoxic effects were measured. PPF-induced SNHG6 expression change in HiPSC-CMs were monitored by qRT-PCR. SNHG6 was downregulated in HiPSC-CMs to examine its role in PPF-induced cardiac cytotoxicity. The expression of competing endogenous RNA (ceRNA) candidate of SNHG6, human microRNA-186-5p (hsa-miR-186-5p) was also investigated in PPF-exposed HiPSC-CMs. Functions of hsa-miR-186-5p were further investigated in PPF-exposed and SNHG6-downregulated HiPSC-CMs. RESULTS: PPF induced significant cytotoxicity, as well as SNHG6 upregulation in HiPSC-CMs. SNHG6 downregulation had rescuing effects on PPF-induced cardiac cytotoxicity. Dual-luciferase activity assay confirmed that hsa-miR-186-5p was the ceRNA candidate of SNHG6. QRT-PCR showed hsa-miR-186-5p expression was reversely correlated with SNHG6 in PPF-exposed HiPSC-CMs. Suppressing hsa-miR-186-5p reduced the rescuing effects of SNHG6-downregulation on PPF-induced cardiac cytotoxicity. CONCLUSIONS: SNHG6/hsa-miR-186-5p can modulate PPF-induced cardiac cytotoxicity in HiPSC-CMs, and thus may be a future drug target to prevent PPF infusion syndrome.